Number and size of human X chromosome fragments transferred to mouse cells by chromosome-mediated gene transfer. - Olsen, A S (1981)
Labeled probes of unique-sequence human X chromosomal deoxyribonucleic acid, prepared by two different procedures, were used to measure the amount of human X chromosomal deoxyribonucleic acid in 12 mouse cell lines expressing human hypoxanthine phosphoribosyltransferase after chromosome-mediated gene transfer. The amount of X chromosomal deoxyribonucleic acid detected by this procedure ranged from undetectable levels in the three stable transformants and some unstable transformants examined to about 20% of the human X chromosome in two unstable transformants. Reassociation kinetics of the X chromosomal probe with deoxyribonucleic acid from the two unstable transformants containing 15 to 20% of the human X chromosome indicate that a single copy of these sequences is present. In one of these lines, the X chromosomal sequences exist as multiple fragments which were not concordantly segregated when the cells were selected for loss of hprt.